Plan de mejoramiento enfocado al clima organizacional de la empresa Indupan S.A.S. (2021)
The present work aims to develop a plan to improve the work environment of the company INDUPAN S.A.S based on the diagnosis made by the Rensis Likert questionnaire method. A random representative sample of 20 employees of the organization, belonging to the administrative part, was taken to whom a written survey was applied with 23 questions that covered personal, interpersonal and organizational qualities. After this, the results were graphed and analyzed, obtaining in the Likert classification, a type I system. Strategies applied to the most critical dimensions that were found both in the directive part and in the lower management are then proposed, which are: organizational structure, leadership, communication, motivation and sense of belonging. In such a way that the designed action plan allows Indupan S.A.S to move to a type III (participatory) system.